Penggunaan Teknologi Dalam Pengembangan SDM - Wardatun Nikmah; Afifatul Mukarromah; Dimas Widyansyah; Mochammad Isa Anshori (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The use of technology in human resource (HR) development is one of the strategies to improve the quality, skills, and competencies of HR in order to adapt to environmental changes and future challenges. Technology can be used to support HR management processes, such as recruitment, selection, training, assessment, and career development. Technology can also help create added value for organizations through innovation, creativity, and collaboration. This research aims to examine the influence of technology on HR development in various fields, such as business, education, government, and health. The research method used is a literature study by collecting and analyzing secondary data from various sources. The results show that technology has a positive impact on HR development, such as increasing efficiency, effectiveness, productivity, performance, motivation, satisfaction, loyalty, and commitment of HR. However, technology also poses challenges and barriers to HR development, such as changes in organizational culture, new competency needs, ethical issues, privacy, and data security. Therefore, an appropriate strategy is needed to implement technology in HR development in order to provide optimal benefits for organizations and individuals.